Models for improving cataract surgical rates in southern China - Xu, J (Copyright 2002 British Journal of Ophthalmology, 2002)
Background/aims: Unoperated cataract is the main challenge to blindness reduction in China. This demonstration project in Guangdong Province was designed to test various strategies to improve the cataract surgical rate. Methods: Two strategies (reduction of the cataract surgical fee and training of country doctors in the detection of cataract blindness) were implemented in each of two counties. Both interventions were introduced in a third county. Results: The cataract surgery rate (CSR) per million was 366 in the county where training took place, 588 where the fee was lowered, and 1140 where both interventions took place. The improvement in CSR was highly significant (p<0.001). Conclusions: In southern China, CSR can be increased with community based measures. Sustainability for such measures will be the major future challenge.